Neurovascular and neurometabolic derailment in aging and Alzheimer's disease - Lourenço, Cátia F.; Ledo, Ana; Dias, Cândida; Barbosa, Rui M.; Laranjinha, João (Frontiers in Aging Neuroscience, 2015)
The functional and structural integrity of the brain requires local adjustment of blood flow and regulated delivery of metabolic substrates to meet the metabolic demands imposed by neuronal activation. This process – neurovascular coupling – and ensued alterations of glucose and oxygen metabolism - neurometabolic coupling - are accomplished by concerted communication between neural and vascular cells. Evidence suggests that neuronal-derived nitric oxide (•NO) is a key player in both phenomena. Alterations in the mechanisms underlying the intimate communication between neural cells and vessels ultimately lead to neuronal dysfunction. Both neurovascular and neurometabolic coupling are perturbed during brain aging and in age-related neuropathologies in close association with cognitive decline. However, despite decades of intense investigation, many aspects remain poorly understood, such as the impact of these alterations. In this review, we address neurovascular and neurometabolic derailment in aging and Alzheimer’s disease, discussing its significance in connection with •NO-related pathways.